The Implementation of Ushul-Fiqh Learning in the School Environment to Form Moderate Students’ Religious Character - Bahar, Muchlis (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aimed to analyze the implementation of ushul-fiqh learning in the school environment to form the moderate religious character of students. This study uses a type of field research with descriptive qualitative methods. This research is located in Madrasa Aliyah Nagari Gantung Ciri with a case study research model. The data validity test carried out in this study included triangulation techniques, namely checking the validity of the data through other sources. Based on the research results, the learning of ushul fiqh at Madrasa Aliyah Nagari Gantung Ciri West Sumatra has implemented moderate Islamic education to students in four ways, namely through content, active learning methods, programmed habituation such as deliberation and evaluation.